2000
DOI: 10.1111/1467-646x.00060
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Value Relevance of Consolidated versus Unconsolidated Accounting Information: Evidence from Quoted Spanish Firms

Abstract: In this paper we investigate the value-relevance of consolidated versus parent company accounting information. In particular we investigate the value relevance of the minority interest components of net total assets and earnings as currently reported and under the full entity approach to consolidated reporting. An Edwards-Bell-Ohlson valuation framework is used to generate results. By this means we cast light on the suitability of accounting regulation being developed based upon the entity or parent company th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 15 publications
3
54
1
Order By: Relevance
“…We consolidate the economic and financial information, in line with Abad et al (2000), who highlight the potential limitations of accounting information at the individual level. Individual financial statements have been used in the case of non-consolidated financial statements.…”
Section: Methodsmentioning
confidence: 99%
“…We consolidate the economic and financial information, in line with Abad et al (2000), who highlight the potential limitations of accounting information at the individual level. Individual financial statements have been used in the case of non-consolidated financial statements.…”
Section: Methodsmentioning
confidence: 99%
“…We decided to focus on the consolidated accounting information, given the existing evidence that it is the consolidated information that is being taken into account when valuing the stocks of parent companies. (Abad et al, 2000 finds evidence that for Spanish firms the consolidated information is more value-relevant than the parent company disclosure alone. Moreover, interviews with Spanish financial analysts reveal that valuations of the parent company are based on group rather than individual accounts, unless the parent company's activities are highly differentiated from the rest of the group's.…”
Section: Data Descriptionmentioning
confidence: 97%
“…Previous research on the effect of consolidation on the value relevance of accounting numbers is scant. In [44], the authors find that consolidated accounting numbers in Spain are more value relevant than the parent company disclosure alone where book value has higher value relevance than earnings. Similarly, using Finnish accounting data for domestic and foreign investors, [45] found that consolidated data provide more useful information to both types of investors.…”
Section: Value Relevance Of Accounting Reformsmentioning
confidence: 98%